Working posture analysis of wall building activities in construction works using the OWAS method. Issue 1 (February 2021) - Iqbal, M; Angriani, L; Hasanuddin, I; Erwan, F; Soewardi, H; Hassan, A
Abstract: Activities of construction works are carried out manually and continuously with critical and repetitive working postures. The poor working condition causes fatigue, musculoskeletal disorder, in the worst case could lead to working accident. The paper discussed critical working postures of construction works of house construction project in Indonesia. Three mains activities have been identified to be studied, namely building up the brick wall, plastering the wall, and casting the concrete column. The activities were video recorded, the dimension of the work place and its component were measured and further analyzed in ergonomics laboratory. The postures were studied using Ovako Working Posture Analysis System (OWAS) method to identify their critical levels. The improvements were proposed to remove the critical posture and reduce the risk of injury. Result of the study showed that building up the brick wall was the most critical task since it has 2 critical postures, while plastering the wall and casting the concrete column have 1 critical posture respectively. The propose improvement has successfully removed the critical posture and reduce the risk of injury.